2014
DOI: 10.1080/01621424.2014.964897
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment and Retention of Home Support Workers in Rural Communities

Abstract: This qualitative study examined recruitment and retention of home support workers (HSWs) providing home support in rural communities. Thirty-two participants were recruited across four island-based communities located in British Columbia, Canada. Thematic analysis of interview data revealed several key themes: (a) how the rural context shapes HSWs' employment decisions and opportunities; (b) why people become (and stay) HSWs in rural communities; and (c) how rurality influences the nature and scope of HSWs' wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Research has looked into the best practice of employers with less than 10% staff turnover ( 99 ) and approaches that combine health and social care approaches to workforce development ( 100 ). Workforce issues in rural communities and retention challenges in these areas is an international concern ( 101 103 ). Modelling career success is advocated as a way of enhancing recruitment and retention ( 104 ).…”
Section: Resultsmentioning
confidence: 99%
“…Research has looked into the best practice of employers with less than 10% staff turnover ( 99 ) and approaches that combine health and social care approaches to workforce development ( 100 ). Workforce issues in rural communities and retention challenges in these areas is an international concern ( 101 103 ). Modelling career success is advocated as a way of enhancing recruitment and retention ( 104 ).…”
Section: Resultsmentioning
confidence: 99%
“…One study reported that 86% of UCPs felt rushed and 75% omitted at least one task as a result of insufficient time (Knopp‐Sihota et al., ). Fewer full‐time positions and more casual or on‐call positions with lower wages, as well as unpredictable scheduling, create difficulty for UCPs to develop and manage ongoing relationships with patients (Sharman, ), and prevent them from learning or implementing new skills in their busy work routine (Tayab & Narushima, ). Thus, existing care setting workflows prevent workers from building strong relationships with patients as they are rushing to complete routine activities, thus negatively impacting the quality of care (Aubry et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of paid personal care in the home is provided by unregulated health professionals, mainly women, largely because of relationship and non-monetary rewards, but they face challenges of poor wages, inconsistent scheduling, lack of training, opportunities for advancement, and feeling isolated (Keefe, Knight, Martin-Matthews, & Légaré, 2011). The challenges of retention are exacerbated in rural areas where relationships are complex, and the context of the care needs to be considered by health service provider organizations, going beyond the provision of education and training (Rydenfält et al, 2020;Sharman, 2014). One study based on home support worker experiences suggested team-based approaches, increased control over scheduling, reduction of risks taken, and isolation experienced to enhance retention (Sharman, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The challenges of retention are exacerbated in rural areas where relationships are complex, and the context of the care needs to be considered by health service provider organizations, going beyond the provision of education and training (Rydenfält et al, 2020;Sharman, 2014). One study based on home support worker experiences suggested team-based approaches, increased control over scheduling, reduction of risks taken, and isolation experienced to enhance retention (Sharman, 2014). Even when considering the importance of the health and social service workers to enable older adults to age in place, there have been only 16 studies identified in a scoping reviewnone of them PARthat focused on the retention of home support workers.…”
Section: Literature Reviewmentioning
confidence: 99%